Methane Gas Production Test From Forage Swamp with Ensilase Method As Biogas Plants - Erra Kartika; Nuni Gofar; Sofia Sandi (Sriwijaya Journal of Environment, 2017)
This study aims to test the production of methane gas from forage swamps by ensilase as biogas plants. Treatment levels consisted of 3 treatments P1 (100% Kumpai tembaga grass (Hymenachne acutigluma)), P2 (50% Kumpai tembaga grass (Hymenachne acutigluma) + 50% Kemon air (Neptunia oleracea lour)), P3 (100% Kemon air (Neptunia Oleracea lour)) and 5 replications. The result of the diversity analysis showed that silage swamp silage ensilase process significantly (p <0,05) to methane gas formation. The best composition was obtained from the treatment of P1 Kumpai tembaga grass (Hymenachne acutigluma) 100%.Keywords: Production, Methane, Forage Swamps, Ensilase, Biogas Plants.